On the equivalence problem for bracket-generating distributions - Kaplan, Aroldo (2014)
We describe Tanaka´s version of Cartan Equivalence Method for bracket-generating distributions in a form suited to study the horizontal distributions on period domains and on their boundaries, and apply it to certain polycontact related to the latter.